STUDENTS’ WORK DIARIES: VISUAL IMPRESSIONS OF A PROJECT-BASED LEARNING MODULE - Angelova, Desislava; Vodenova, Pavlina; Raycheva, Regina; Tasheva, Stela (Innovation in Woodworking Industry and Engineering design, 2023)
participating in the Project-Based Learning Module (PBLM) called Design Project, a study module of the Engineering Design (Interior and Furniture Design) Bachelor Program. The following questions related to the diaries are considered in the article: Are students paying enough attention to these diaries as a tool to present their work? To what extent is the submitted information sincere and complete? Are students’ work diaries an effective way of grading each students’ teamwork and the individual members? Based on the analysis made of students’ diaries from Design Project module in four successive years, conclusions and recommendations are made. The aim is to improve the requirements for the preparation of student diaries, so that teachers can use them for grading the work done by teams and their individual members.